Impacts And Perceptions Of Climate Variability On Shea (Vitellaria paradoxa) And African Locust Bean (Parkia biglobosa) In Burkina Faso - (:unkn) unknown (My University, 2023)
This article examines manifestations of climate variability and its impacts on tree species (shea, African locust bean) in agricultural fields through an analysis of the opinion of the field managers. The Likert-type survey form was prepared for this purpose for the collection of primary data in the field. A sample of 110 households out of a total of 480 was selected, and secondary data (rainfall, temperature and wind) were also collected through Burkina Faso’s national meteorological agency. Descriptive statistics were used to analyse the primary data collected. The study revealed that 90% of agroforestry parkland managers perceive climate variability through rainfall, temperature and wind. The meteorological data also showed trends in the variability of rainfall, temperature and wind between 1990 and 2020. They also observed that climate variability has an impact on shea and African locust through the disruption of the phenological phases (foliage, flowering, fruiting and fructification) of the trees, the death of young shea seedlings and stunted growth of shea, as well as the reduction in fruit productivity of both species.
Keywords: African Research